2008
DOI: 10.1016/j.nbt.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

SRP and Sec pathway leader peptides for antibody phage display and antibody fragment production in E. coli

Abstract: Antibody phage display is a key technology for the generation of recombinant (human) antibodies for research, diagnostics and therapy. Most antibody fragments can only be folded correctly in the oxidizing environment of the periplasm of Escherichia coli. A multitude of leader peptides has been used for secretion of antibody::pIII fusion proteins into the periplasm, but a systematic study of their impact on the performance of antibody phage display systems has not been reported so far. In this work we have anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 44 publications
(52 reference statements)
1
41
0
1
Order By: Relevance
“…MalE, PelB, or TorT signal peptides were divided into two groups by their secretion pathways. MalE and PelB signal peptides lead their fusion proteins to the Sec-dependent pathway, and TorT signal peptide leads its fusion protein to the signal recognition particle pathway for translocation into the periplasm (Thie et al 2008). Our results suggested that expression of soluble aglycosylated rhFcγRI was possible via both secretion pathways of E. coli.…”
Section: Discussionmentioning
confidence: 66%
“…MalE, PelB, or TorT signal peptides were divided into two groups by their secretion pathways. MalE and PelB signal peptides lead their fusion proteins to the Sec-dependent pathway, and TorT signal peptide leads its fusion protein to the signal recognition particle pathway for translocation into the periplasm (Thie et al 2008). Our results suggested that expression of soluble aglycosylated rhFcγRI was possible via both secretion pathways of E. coli.…”
Section: Discussionmentioning
confidence: 66%
“…Our results showed that the mature cutinase was partially located in the periplasm, while some was secreted into the culture medium (14). Secretion into the culture medium was not unexpected, since similar phenomena have been observed in the expression of other secretory proteins (15)(16)(17)(18)(19). After optimization of the cultivation conditions in shake flasks, the cutinase activity in the culture medium reached 149.2 U/ml (326 mg/liter) 52 h postinduction (14).…”
mentioning
confidence: 64%
“…Because the disulfide bonds of the newly synthesized preprotein can only be formed in the oxidizing environment of periplasm, the mechanism for the translocation of the nascent unfolded polypeptide chain from the translation site in the cytoplasm across the periplasm membrane could be a key determinant for the folding and, consequently, for the expression of the displayed protein on the phage surface (25)(26)(27)(28)(29)(30)(31). Alternative sequences in the signal peptide region have been known to modulate the expression level and folding quality of the displayed protein (25,27,31), but difficulty remains in identifying optimum signal sequences in a vast sequence space for some sc-dsFv constructs.…”
Section: Discussionmentioning
confidence: 99%
“…The key discovery is that the signal sequence variants of the sc-dsFv-pIII fusion protein have varying effects in directing the sc-dsFv expression on the recombinant phage surface. The signal sequence has been known to be responsible for the Sec system-dependent translocation of the pIII fusion protein from the translation site in the cytoplasm to the periplasm membrane (25)(26)(27)(28)(29)(30)(31), a critical process for the integration of the displayed protein on the recombinant phage surface (32). But the optimal signal sequences for the translocation of the pIII fusion protein were not known.…”
mentioning
confidence: 99%